2022
DOI: 10.1039/d2tc03756d
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure dependence of the microstructure and microwave dielectric properties of (SrxCa1−x)(Zr0.95Ti0.05)O3 (0 ≤ x ≤ 1) perovskite ceramics

Abstract: Solid-state reaction process has been used to fabricate (SrxCa1-x)(Zr0.95Ti0.05)O3 (0 ≤ x ≤ 1) ceramics, the crystal structure dependence of microstructure and microwave dielectric properties has been investigated. The grain...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…8 The change in the Ca/Sr ratio can affect the crystalline phase and the dielectric properties of the (Ca x Sr (1− x ) )ZrO 3 ceramics. 11 The melting temperature of CaZrO 3 ( T m = 2340 °C) is lower than that of SrZrO 3 ( T m = 2750 °C) and the Ca 2+ radius (1.34 Å) is smaller than that of Sr 2+ (1.44 Å), and the lattice strain will be reduced when Ca is substituted to the Sr-site in the lattice. Lower sintering temperature can be obtained, and the grain size in the (Ca,Sr)(Zr,Ti)O 3 ceramics increases significantly as the Ca/Sr ratio increases.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…8 The change in the Ca/Sr ratio can affect the crystalline phase and the dielectric properties of the (Ca x Sr (1− x ) )ZrO 3 ceramics. 11 The melting temperature of CaZrO 3 ( T m = 2340 °C) is lower than that of SrZrO 3 ( T m = 2750 °C) and the Ca 2+ radius (1.34 Å) is smaller than that of Sr 2+ (1.44 Å), and the lattice strain will be reduced when Ca is substituted to the Sr-site in the lattice. Lower sintering temperature can be obtained, and the grain size in the (Ca,Sr)(Zr,Ti)O 3 ceramics increases significantly as the Ca/Sr ratio increases.…”
Section: Introductionmentioning
confidence: 94%
“…Through group theory analysis, it is found that there are a total of 24 Raman active modes. [11][12][13]18,19 Fig. 8 presents the Raman spectra of the CSZTY (x = 0, 0.01, 0.025, 0.05, 0.10, 0.15, 0.20) ceramics in the 100 cm À1 to 900 cm À1 frequency range.…”
Section: Materials Advances Papermentioning
confidence: 99%
See 2 more Smart Citations
“…Parida et al 16 also investigated that the microwave dielectric properties vary in the Sr(Zr x Ti 1− x )O 3 (0 ≤ x ≤ 1) system and concluded that the ε r value decreased from 253.0 to 25.0 with increasing Zr content and the τ f value was +1771.0 ppm °C −1 for SrTiO 3 that decreased to −82.0 ppm °C −1 for SrZrO 3 . Wang et al 17 investigated the perovskite Sr(Zr 0.95 Ti 0.05 )O 3 ceramic that possessed optimum microwave dielectric properties of ε r ∼ 36.4, Q × f ∼ 26 300 GHz and τ f ∼ −2.5 ppm °C −1 . However, the modified CaZrO 3 did not satisfy practical requirements due to their poor microwave dielectric properties.…”
Section: Introductionmentioning
confidence: 99%